2016
DOI: 10.1111/jnc.13894
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 haploinsufficiency induces a BNIP3‐dependent decrease in mitophagy in neurons: relevance to Dominant Optic Atrophy

Abstract: Dominant optic atrophy (DOA) is because of mutations in the mitochondrial protein OPA1. The disease principally affects retinal ganglion cells, whose axons degenerate leading to vision impairments, and sometimes other neuronal phenotypes. The exact mechanisms underlying DOA pathogenesis are not known. We previously demonstrated that the main role of OPA1, as a mitochondrial fusogenic and anti-apoptotic protein, are inhibited by interaction with the stress inducible pro-apoptotic BNIP3 protein. Because BNIP3 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…This is in agreement with recent reports documenting the alteration of mitophagic and autophagic activities in OPA1-related diseases [12,47]. Studies on in vitro neuronal models and an in vivo mouse model of OPA1 insufficiency have shown that the down-regulation of OPA1 reduces the level of BNIP3 (BCL2/adenovirus E1B 19 kDa interacting protein 3) [47], previously implicated in the induction of mitophagy and autophagy [48]. While the reduction of mitophagy and autophagy is not itself sufficient to induce spontaneous apoptotic cell death, it contributes greatly to the susceptibility of neurons to chronic and acute stress [28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with recent reports documenting the alteration of mitophagic and autophagic activities in OPA1-related diseases [12,47]. Studies on in vitro neuronal models and an in vivo mouse model of OPA1 insufficiency have shown that the down-regulation of OPA1 reduces the level of BNIP3 (BCL2/adenovirus E1B 19 kDa interacting protein 3) [47], previously implicated in the induction of mitophagy and autophagy [48]. While the reduction of mitophagy and autophagy is not itself sufficient to induce spontaneous apoptotic cell death, it contributes greatly to the susceptibility of neurons to chronic and acute stress [28].…”
Section: Discussionsupporting
confidence: 94%
“…We hypothesize that the reduction of autophagy and mitophagy, particularly the absence of stimulation of these pathways, may be part of the pathophysiology of OPA1 mutations leading to haploinsufficiency. This is in agreement with recent reports documenting the alteration of mitophagic and autophagic activities in OPA1-related diseases [12,47]. Studies on in vitro neuronal models and an in vivo mouse model of OPA1 insufficiency have shown that the down-regulation of OPA1 reduces the level of BNIP3 (BCL2/adenovirus E1B 19 kDa interacting protein 3) [47], previously implicated in the induction of mitophagy and autophagy [48].…”
Section: Discussionsupporting
confidence: 92%
“…in vitro experiments revealed an interaction of OPA1 with BNIP3’s carboxyl‐terminus in a phosphorylation‐dependent manner, which led to disassembly of OPA1 complexes and prompted cytochrome c release . Interestingly, cortical neurons showed a correlation of BNIP3 levels and disease progression in mutant OPA1 mice providing further support for a functional connection between OPA1 and BNIP3 . OPA1 was also identified as parkin interaction partner in proteomics studies combining tandem affinity purification and mass spectrometry profiling .…”
Section: Mitochondrial Membrane Organizationmentioning
confidence: 89%
“…[98][99][100][101] Interestingly, cortical neurons showed a correlation of BNIP3 levels and disease progression in mutant OPA1 mice providing further support for a functional connection between OPA1 and BNIP3. 102 OPA1 was also identified as parkin interaction partner in proteomics studies combining tandem affinity purification and mass spectrometry profiling. 103 The parkin E3 ubiquitin protein ligase is part of an ubiquitin ligase complex recruited to the mitochondrial outer membrane upon loss of the membrane potential Δψ.…”
Section: Opa1mentioning
confidence: 99%
“…Thirdly, it is possible that mitophagy is not actually increased in RGCs in OPA1 knock down. Indeed, Belenguer showed that BNIP3 dependent mitophagy is actually decreased in a neuronal model of OPA1 knock-down (Moulis et al, 2017 ). Given that we previously showed that mitophagy declines with maturity in fibroblasts (Diot et al, 2015 ), we suggest that their neuronal cultures may not reflect in vivo mature RGCs.…”
Section: Discussionmentioning
confidence: 99%